Analysis of The Cost of Production of Tofu by Using The Full Costing Method (Case Study at Tofu Factory) - Dyah Sari Ningrum; Netty Herawaty; Fredy Olimsar (Greenation Research & Yayasan Global Resarch National, 2025)
Accurate determination of the cost of goods produced is very important for business actors to know the amount of costs incurred in the production process and as a basis for setting selling prices. This study aims to analyze the calculation of the cost of production of tofu using the full costing method in a tofu factory. The full costing method takes into account all production costs, both raw material costs, direct labor, and fixed and variable factory overhead costs. This research uses a case study approach with data collection through observation, interviews, and documentation at the tofu factory which is the object of research. The results of the analysis show that the calculation of the cost of production using the full costing method provides a more complete and accurate picture compared to the method that has been used by the factory. Thus, the application of this method can help business owners in making selling price decisions, evaluating cost efficiency, and increasing company profits.